2019
DOI: 10.1111/jbg.12393
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters and season effects for semen traits in three pig breeds of South China

Abstract: The economic profitability of a boar station largely depends on semen quantity and quality traits. However, genetic analysis of semen traits has not yet been done in the boar population in China. In this study, we aimed to estimate genetic parameters for semen traits and the influence of seasons on these traits by using data of Duroc, Landrace and Yorkshire boars in South China. The following four semen traits were analysed: semen volume (ml; VOL), sperm concentration (10 6 /ml; DEN), sperm motility (MOT) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Our data are also comparable to those published for other species. For example, Li et al [16] reported similar heritabilities in pigs (Landrace boars), ranging from 0.11 to 0.23 (for the MOT and SC traits, respectively), and Karoui et al [7], showed a similar pattern, obtaining heritabilities from 0.16 to 0.22 (for the MOT and VOL traits, respectively) in Holstein bulls. In contrast, other researchers found higher heritabilities for the MOT trait, surpassing those found in the VOL or SC traits.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Our data are also comparable to those published for other species. For example, Li et al [16] reported similar heritabilities in pigs (Landrace boars), ranging from 0.11 to 0.23 (for the MOT and SC traits, respectively), and Karoui et al [7], showed a similar pattern, obtaining heritabilities from 0.16 to 0.22 (for the MOT and VOL traits, respectively) in Holstein bulls. In contrast, other researchers found higher heritabilities for the MOT trait, surpassing those found in the VOL or SC traits.…”
Section: Discussionmentioning
confidence: 88%
“…For example, in Ethiopian sheep, Rege et al [9] found values of 0.32 and 0.27 for the MOT trait in 9 and 12-month-old rams, respectively. For Holstein bulls, Druet et al [5] obtained a heritability of 0.43, and Li et al [16], found values of 0.26 and 0.42 in Yorkshire and Duroc pig breeds, respectively. Heritability estimates found in the present study and the variability found in different breeds and species point towards the opportunity for genetic improvement of some semen traits through selective breeding.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Semen quality is affected by a number of factors, such as the age of collection [34], season [52], breed [53], and individual response to the environment [54]. Current studies on the semen quality of clones and non-clones indicate that cloning technology can also affect semen quality [21,34], but contradictory results are observed in some parameters.…”
Section: Discussionmentioning
confidence: 99%
“…However, both genetic and population diversity can influence the variance components. In addition, most of the studies related to semen traits are based on animal models or repeatability models (Wolf, 2009b;Marques et al, 2017;Li et al, 2019), and there is little research using random RR models for semen traits. Compared with animal models and repeatability models (Oh et al, 2006), the RR model demonstrated change of meaning and covariance along with age (Schaeffer, 2004).…”
Section: Introductionmentioning
confidence: 99%